The Effectiveness of Proprioceptive Neuromuscular Facilitation (PNF) on Balance and Fall Risk in Older Adults: A Systematic Literature Review - Putri, Rheifani Salsabila; Santoso, Iman (Universitas Muhammadiyah Surakarta, 2025)
Introduction: Proprioceptive Neuromuscular Facilitation (PNF) is an exercise method that focuses on improving neuromuscular control through proprioceptor stimulation. PNF is more commonly used in neurological therapy, but further research is needed regarding its ability to address musculoskeletal issues, such as balance and fall risk in the elderly. This study aims to review the PNF approach and analyse its effectiveness in improving balance and reducing the risk of falls in the elderly based on existing literature reviews. Methods: This study uses a simple literature review method. Data were collected through searches in research article databases such as Google Scholar, Crossref, ProQuest, PubMed, Science Direct, Scopus, and Semantic Scholar. Inclusion criteria for this article included studies published between 2015 and 2025, experimental research designs, and the application of Proprioceptive Neuromuscular Facilitation (PNF) in the elderly. Results: A review of six previous studies showed that PNF exercises had a positive effect on improving balance and reducing the risk of falls in the elderly. Conclusion: Proprioceptive Neuromuscular Facilitation (PNF) has been proven effective in improving balance and functional range associated with a reduced risk of falls in the elderly. With these benefits, PNF can be an important component of fall prevention programmes and improving the quality of life for the elderly.